A path twice traveled my journey as a historian of China - Cohen, Paul A. (The Fairbank Center for Chinese Studies at Harvard University, 2019)
"Cohen, one of the West's pre-eminent historians of China, traces the development of his work from its inception in the early 1960s to the present, offering fresh perspectives that consistently challenge readers to think more deeply about China and the historical craft in general"--Provided by publisher.